EVALUATION OF ANTI PYRETIC ACTIVITY OF AERIAL PARTS OF PHYLLANTHUS LONGIFLORUS HEYNE EX HOOK. - Jesupillai, M; Thillai Arasu, P; Jasemine, S; Bharathidhasan, P (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The present study was designed to investigate antipyretic activity of aerial parts of Phyllanthus longiflorus (PHL) in albino rats. Methanol and aqueous extracts of PHL at the doses 100 and 200 mg/kg body weight significantly (p < 0.001) normalized the Brewer's yeast induced pyrexia in a dose dependant manner. Paracetamol 150 mg/kg body weight was included in the study as reference drug. Â Keywords: Phyllanthus longiflorus, yeast, anti pyretic, aerial parts.Â